2019
DOI: 10.1108/mrr-02-2018-0098
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of team creativity: a person-environment fit perspective

Abstract: Purpose Limited research where team creativity (TC) is positioned as an independent variable constitutes a weak point in the body of knowledge. This paper aims to offer three contributions to address this research gap: empirical research that has been conducted on the outcomes of TC is summarized; a person–environment fit perspective is applied to develop a conceptual model for TC; and directions for future empirical research are proposed. Design/methodology/approach A literature review is conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…POF as a construct is rooted in interactional psychology. This 'fit' has been explored with respect to variables like work group, organization, supervisors, retention, organizational attraction and turnover intention (Bam et al, 2019). Perception of a sample of insurance professionals has driven Sahu (2018) to conclude that empowerment of employees at work explains significant variance in outcome variables like fit with organization and job satisfaction.…”
Section: Person-organization Fitmentioning
confidence: 99%
“…POF as a construct is rooted in interactional psychology. This 'fit' has been explored with respect to variables like work group, organization, supervisors, retention, organizational attraction and turnover intention (Bam et al, 2019). Perception of a sample of insurance professionals has driven Sahu (2018) to conclude that empowerment of employees at work explains significant variance in outcome variables like fit with organization and job satisfaction.…”
Section: Person-organization Fitmentioning
confidence: 99%
“…Moreover, the fit between workplace environment and employee characteristics makes the resources the organization provides to match the employees’ needs well (Wojtczuk-Turek and Turek, 2016). This is the source of motivation that encourages employees to perform their work more effectively (Bam et al , 2019). Therefore, the P-E theory has been used extensively to explain employees’ work attitudes, well-being and performance outcomes (Guan et al , 2021; Bam et al , 2019; Rani and Samuel, 2016; Saraç et al , 2017; Wojtczuk-Turek and Turek, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is the source of motivation that encourages employees to perform their work more effectively (Bam et al , 2019). Therefore, the P-E theory has been used extensively to explain employees’ work attitudes, well-being and performance outcomes (Guan et al , 2021; Bam et al , 2019; Rani and Samuel, 2016; Saraç et al , 2017; Wojtczuk-Turek and Turek, 2016). For example, Andela and van der Doef (2018) found that employees who exhibited a high level of P-E fit tended to demonstrate a high level of job satisfaction and a low level of burnout and turnover intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Performance evaluations in organizations show the positive impact of plural creativity on the work performed individually (Bissola & Imperatori, 2011;Cirella, 2016); goals, deadlines and results are easily achieved through teamwork, helping to keep the organization's good performance (Jiang & Zhang, 2014). In this way, plural creativity is a potential source for reaching complex creative ideas, for problem-solving, and contributes to the achievement of high levels of innovation and performance in teams (Bam et al, 2019), organizational survival and quality in the results expected by the organization.…”
Section: Advantage Competitivementioning
confidence: 99%